2023
DOI: 10.3390/nano13061083
|View full text |Cite
|
Sign up to set email alerts
|

PF127 Hydrogel-Based Delivery of Exosomal CTNNB1 from Mesenchymal Stem Cells Induces Osteogenic Differentiation during the Repair of Alveolar Bone Defects

Abstract: Pluronic F127 (PF127) hydrogel has been highlighted as a promising biomaterial for bone regeneration, but the specific molecular mechanism remains largely unknown. Herein, we addressed this issue in a temperature-responsive PF127 hydrogel loaded with bone marrow mesenchymal stem cells (BMSCs)-derived exosomes (Exos) (PF127 hydrogel@BMSC-Exos) during alveolar bone regeneration. Genes enriched in BMSC-Exos and upregulated during the osteogenic differentiation of BMSCs and their downstream regulators were predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…JUN families include c-Jun is involved in the expression of various inflammatory genes by binding to their transcription factor binding sites. The c-Jun binds to the proximal IL-6 promoter and promotes IL-6 production which has been associated with accelerated osteoclastogenesis and elevated bone resorption (35). CTNNB1 encodes b-catenin which is a key player in the canonical Wnt/b-catenin signaling pathway (36), and has been shown regulate osteoblastic differentiation and osteoclastogenesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…JUN families include c-Jun is involved in the expression of various inflammatory genes by binding to their transcription factor binding sites. The c-Jun binds to the proximal IL-6 promoter and promotes IL-6 production which has been associated with accelerated osteoclastogenesis and elevated bone resorption (35). CTNNB1 encodes b-catenin which is a key player in the canonical Wnt/b-catenin signaling pathway (36), and has been shown regulate osteoblastic differentiation and osteoclastogenesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…This composite patch showed enhanced skin wound healing in rat model, a promising and effective strategy for clinical applications of therapeutic exosomes [30]. Recent studies supporting application of exosomes with electroconductive hydrogels highlight stable integration of exosome in nanofibrous structures without compromising hydrogel electrical activity and mechanical properties while maintaining therapeutic properties of the exosomes [63,64,95,96]. Nanofibers have been explored for isolation, delivery, biosensing, bioimaging, preservation and spatial analysis of exosome [37,[97][98][99].…”
Section: Electrospinning With Exosomesmentioning
confidence: 99%
“…Extensive research has been conducted using MSC therapies in both animal models and patients, employing different methods such as direct MSC injection, seeding MSCs on synthetic scaffolds, utilizing gene-modified MSCs, and employing allogenic MSC application. The literature surrounding the use of genetically modified MSCs as well as MSCs on synthetic scaffolds has shown positive results in terms of promoting osteogenic differentiation of MSCs and bone regrowth in both animal and human studies [87,88]. While there has been less research on non-scaffolded ASCs in bone regrowth, results from some studies have shown that the use of non-scaffolded MSCs can induce bone regrowth in patients with bone lesions or defects [89].…”
Section: Msc-based Strategies For Bone Regeneration In Vivomentioning
confidence: 99%